1996
DOI: 10.1046/j.1523-1739.1996.10041229.x
|View full text |Cite
|
Sign up to set email alerts
|

A Century of Plant Species Loss from an Isolated Fragment of Lowland Tropical Rain Forest

Abstract: An isolated 4‐ha fragment of lowland tropical rain forest has been preserved in the Singapore Botanic Gardens since their founding in 1859. The Botanic Gardens’Jungle has recently had enumerated all woody stems 5 cm diameter at breast height (dbh) and larger and the complete vascular plant flora inventoried. This inventory can be compared with the historic record of the flora of the Gardens’Jungle obtained from the extensive collection of herbarium specimens dating back to the 1890s. Of the 448 historically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
1
11

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(100 citation statements)
references
References 15 publications
2
86
1
11
Order By: Relevance
“…Fragmentos florestais pequenos e isolados, originados por desmatamentos em uma paisagem originalmente coberta por floresta, apresentam uma tendência ao empobrecimento, devido à incapacidade de regeneração de muitas populações nessas condições (Turner et al 1996). A Reserva da CUASO não apenas é isolada hoje, como também o foi, em um grau provavelmente crescente ao longo do tempo, durante todo o processo de sucessão ecológica que deu origem à sua cobertura florestal atual.…”
Section: Discussionunclassified
“…Fragmentos florestais pequenos e isolados, originados por desmatamentos em uma paisagem originalmente coberta por floresta, apresentam uma tendência ao empobrecimento, devido à incapacidade de regeneração de muitas populações nessas condições (Turner et al 1996). A Reserva da CUASO não apenas é isolada hoje, como também o foi, em um grau provavelmente crescente ao longo do tempo, durante todo o processo de sucessão ecológica que deu origem à sua cobertura florestal atual.…”
Section: Discussionunclassified
“…In particular, species with large local populations are regionally common (i.e., high probability of occurring at any given habitable site), whereas those characterized by small population sizes are regionally rare. Although several hypotheses, ranging from niche-breadth differences to sampling artifact, provide equally plausible explanations for this relationship (Gotelli and Simberloff 1987;Collins and Glenn 1997;Gaston et al 1997;van Rensberg et al 2000), only one hypothesis predicts how modifications to the regional distributional extent of a species assemblage is expected to alter both demographic and community-level processes.…”
mentioning
confidence: 99%
“…We also observed that O. porosa populations presented lower size hierarchy (i.e., less dominance of larger trees) in the more disturbed areas than in the undisturbed areas, suggesting that logging and fragmentation affect the structure of this species, possibly impacting the rates of reproduction and fecundity, which could lead to local extinction (Turner et al 1996;ArroyoRodríguez et al 2007).…”
Section: Discussionmentioning
confidence: 61%
“…For example, in fragments subjected to selective logging, tree removal creates gaps in which light intensity and ground humidity are modified, increasing the edge effects (Broadbent et al 2008) and affecting several ecological processes (Laurance et al 2011), including the survival of large trees (Laurance et al 2000). There is therefore potential synergism between selective logging and forest fragmentation affecting ecological processes, which in turn influences the distribution and structure of plant populations (Turner et al 1996;Hill & Curran 2003;Arroyo-Rodriguez et al 2007). …”
Section: Introductionmentioning
confidence: 99%